2015
DOI: 10.3748/wjg.v21.i32.9656
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of anastomotic complications of esophagojejunostomy after laparoscopic total gastrectomy

Abstract: The incidence of anastomotic complications associated with EJS was not different between LTG and OTG. Anastomotic stenosis was relatively common when the OrVil™ device was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
62
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(81 citation statements)
references
References 75 publications
11
62
1
7
Order By: Relevance
“…With regards to total gastrectomy, incidence of leakage ranges between 0 and 17% [14][15][16]. Increased leakage-related mortality was described as 19-64%, with higher mortality after surgical compared to conservative/endoscopic treatment [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…With regards to total gastrectomy, incidence of leakage ranges between 0 and 17% [14][15][16]. Increased leakage-related mortality was described as 19-64%, with higher mortality after surgical compared to conservative/endoscopic treatment [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…4 -6 In addition, a meta-analysis looking specifically at complications found no significant differences in anastomotic leakage and stenosis in laparoscopic vs open gastrectomies. 7 Despite the slow adoption of minimally invasive total gastrectomy in the USA, we demonstrated that laparoscopic total gastrectomy has good oncological outcomes in a case series of 12 patients. 8 Several other series of single institution experiences have been reported from Asia and Western Europe.…”
Section: Introductionmentioning
confidence: 80%
“…Even if compared with the trans orally inserted anvil approach for EJA (OrVil) [8,9], our technique seems to be equally easy to be reproduced and safe, with a lower risk of intrathoracic infection [10]. Anastomosis performed with ‘OrVil' technique are also more likely to develop stenosis, and the reported overall complication rate (including non-anastomotic complications) is still high [11].…”
Section: Discussionmentioning
confidence: 99%